2020
DOI: 10.2217/nmt-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mexiletine in Amyotrophic Lateral Sclerosis: A Systematic Review of Randomized Controlled Trials

Abstract: Background: Mexiletine is a potential drug in amyotrophic lateral sclerosis (ALS) that has been tested in clinical trials. The objective of this study was to determine the efficacy and safety of mexiletine in ALS via systematic review of existing evidences. Materials & methods: Relevant records were searched using major healthcare electronic databases. Data on functional disability, impairment, survival, muscle cramp frequency and severity, and adverse events were obtained. Results & conclusion: Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As of July 2023, there were only four indexed research studies on ALS from the Philippines [ [10] , [11] , [12] , [13] ]. Five of the included articles in this study investigated ALS in Filipino populations but were not authored by Filipinos nor affiliated with Philippine institutions [ [14] , [15] , [16] , [17] , [18] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As of July 2023, there were only four indexed research studies on ALS from the Philippines [ [10] , [11] , [12] , [13] ]. Five of the included articles in this study investigated ALS in Filipino populations but were not authored by Filipinos nor affiliated with Philippine institutions [ [14] , [15] , [16] , [17] , [18] ].…”
Section: Resultsmentioning
confidence: 99%
“…The recently approved drug for ALS, sodium phenylbutyrate + taurursodiol, is also not yet available in the country for commercial or compassionate use. The lack of available proven treatment options in the country may be reason why two of the included studies are systematic reviews evaluating the utility of perampanel and mexiletine in treating ALS [ 11 , 13 ]. In the study by Adiao and colleagues, three randomized trials were analyzed on the effect of mexiletene on ALS functional rating scale revised (ALSFRS-R), ALS impairment, survival, muscle cramps, and safety and tolerability.…”
Section: Resultsmentioning
confidence: 99%
“…A phase 2 trial demonstrated that it could reduce hyperexcitability ( Weiss et al, 2021 ). A systematic review indicated that mexiletine could not prolong survival, but it could significantly reduce the severity and frequency of muscle cramps ( Adiao et al, 2020 ). Therefore, although mexiletine may not prolong survival, it could be used to treat muscle cramps in patients with ALS.…”
Section: Drugsmentioning
confidence: 99%
“…Recently, mexiletine has been tested for its efficacy in ALS due to its effect in reducing muscle cramps in Machado-Joseph disease. Although results showed no effect on the functional disability, impairment and survival in ALS, mexiletine induced a significant improvement in muscle cramp severity and frequency [ 68 , 69 ].…”
Section: Current Clinical Treatmentsmentioning
confidence: 99%